The Impacts of Household Financial Stress, Resilience, Social Support, and Other Adversities on the Psychological Distress of Western Sydney Parents. (22nd May 2017) - Taylor, Melanie; Stevens, Garry; Agho, Kingsley; Raphael, Beverley
Abstract : This study investigated the prevalence of psychological distress among parents in Western Sydney households and examined its relationship with household financial, family and life stressors, and potential resilience factors. As part of a longer-term study, parents from Western Sydney, New South Wales (NSW), completed computer-assisted telephone interviews (CATI) in May 2011 (N = 439 ). Respondents were primary caregivers of at least one child (aged 4–16). Responses were weighted to reflect the Western Sydney population. Multivariate analyses were conducted to examine the relationship between parent experiences of stressor and resilience factors and reported psychological distress. Overall, 10.7% (95% CI: 7.8, 14.5) reported experiencing high/very high levels of psychological distress. Multivariate analysis indicated that financial hardship factors formed the strongest associations with psychological distress particularly housing and job security factors and, specifically, inability to meet mortgage/rent payments (O R = 5.15, 95% CI: 1.74–15.25, p = 0 . 003 ), poor self-rated health (O R = 4.48, 95% CI: 1.88–10.64, p = 0 . 001 ), adult job loss (O R = 3.77, 95% CI: 1.33–10.66, p = 0 . 013 ), and other family/life events (O R = 2.30, 95% CI: 1.05–5.03, p = 0 . 037 ). High personal resilience was common within this parent population and was a significant protective factor for high psychological distress (O R = 0.14, 95% CI: 0.06–0.34, p < 0 . 001 ). The findings support the development of targeted interventions to promote parent coping strategies in the context of household financial hardship.